2019
DOI: 10.3390/catal9010075
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide as a Catalyst in Biodiesel Production

Abstract: The discovery of alternative fuels that can replace conventional fuels has become the goal of many scientific researches. Biodiesel is produced from vegetable oils through a transesterification reaction that converts triglycerides into fatty acid methyl esters (FAME), with the use of a low molecular weight alcohol, in different reaction conditions and with different types of catalysts. Titanium dioxide has shown a high potential as heterogeneous catalyst due to high surface area, strong metal support interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 51 publications
(64 reference statements)
0
34
0
1
Order By: Relevance
“…C. Carlucci et al [97] used sulfated titanium (TiO2/SO4) as a catalyst instead of a strong acid in the acid transesterification of soybean and castor oils. The maximum yield at 120 o C in 60 min was 40%.…”
Section: Acid Catalyst Transesterificationmentioning
confidence: 99%
“…C. Carlucci et al [97] used sulfated titanium (TiO2/SO4) as a catalyst instead of a strong acid in the acid transesterification of soybean and castor oils. The maximum yield at 120 o C in 60 min was 40%.…”
Section: Acid Catalyst Transesterificationmentioning
confidence: 99%
“…Titanium-dioxide-based catalysts were also investigated [85]. Gardy et al reported that a novel, efficient, and recyclable mesoporous TiO 2 /PrSO 3 H solid acid nanocatalyst was synthesized by the post-synthetic grafting of propyl sulfonic acid groups onto a mixed phase of a TiO 2 support.…”
Section: Tio 2 -Based Catalystsmentioning
confidence: 99%
“…1) the increase of surface area due to the nano-crystalline structure of the catalyst and the acid sites (active sites), dispersed in large surface area, thus providing higher volume surface to facilitate the diffusion of reactants and reagent molecules [39].…”
Section: T31 Catalyst Characterizationmentioning
confidence: 99%